Anxiety type modulates immediate versus delayed engagement of attention‐related brain regions. Issue 5 (1st August 2013) - Spielberg, Jeffrey M.; De, Angeline A.; Bredemeier, Keith; Heller, Wendy; Engels, Anna S.; Warren, Stacie L.; Crocker, Laura D.; Sutton, Bradley P.; Miller, Gregory A.
Abstract Background Habituation of the fear response, critical for the treatment of anxiety, is inconsistently observed during exposure to threatening stimuli. One potential explanation for this inconsistency is differential attentional engagement with negatively valenced stimuli as a function of anxiety type. Methods The present study tested this hypothesis by examining patterns of neural habituation associated with anxious arousal, characterized by panic symptoms and immediate engagement with negatively valenced stimuli, versus anxious apprehension, characterized by engagement in worry to distract from negatively valenced stimuli. Results As predicted, the two anxiety types evidenced distinct patterns of attentional engagement. Anxious arousal was associated with immediate activation in attention‐related brain regions that habituated over time, whereas anxious apprehension was associated with delayed activation in attention‐related brain regions that occurred only after habituation in a worry‐related brain region. Conclusions Results further elucidate mechanisms involved in attention to negatively valenced stimuli and indicate that anxiety is a heterogeneous construct with regard to attention to such stimuli.